Fosfowash: Early proof of concept study investigating intravesical fosfomycin for recurrent urinary tract infections - Welk, Blayne; Munday, Christopher; Burton, Jeremy; Baverstock, Richard J. (Canadian Urological Association Journal, 2021)
NA, research letter